P34 Detecting deficits in cai patients: clinical measures of functional performance compared to percieved measures of insability. (17th September 2017) - Madsen, LP; Hall, EA; Docherty, CL
Abstract : Study Design: Cross-sectional Study. Objectives: To measure functional performance among patients with and without unilateral Chronic Ankle Instability (CAI) and compare objective outcomes to subjective reports of instability. Background: Functional performance tests (FPTs) can be used to measure both subjective reports of instability and objective deficits in physical function among patients with CAI. However, little research has been conducted to identify FPTs that are sensitive enough to measure both subjective and objective deficits associated with CAI. Methods: Twenty-five subjects with CAI (10 males, 15 females; 20.6±2.9 years, 168.8±8.4 cm, 66.5±12.9 kg) and 25 healthy, matched controls (10 males, 15 females; 20.0±2.5 years, 171.1±9.2 cm, 68.6±12.0 kg) completed five unilateral FPTs in random order on each limb: side hop, 6-metre crossover hop, figure-8 hop, triple crossover hop, and lateral hop. After completing a test, subjects were asked to rate their perceptions of instability for both limbs using a visual analogue scale from 0–100. Physical function limb symmetry values and perceived instability limb symmetry values were then calculated for each subject. Two separate multivariate analyses of variance (MANOVAs) were completed to identify group differences in 1) physical function symmetry values and 2) perceived instability symmetry values. Results: There was no significant difference between groups in physical function symmetry values for any of the five FPTs (p>0.05). However, perceived instability symmetry values for the side hop (F1, 48 =6.43, p=0.01), 6-metre hop (F1, 48 =4.36, p=0.04), figure-8 hop (F1, 48 =4.32, p=0.04), and the lateral hop (F1, 48 =3.64, p=0.04) were statistically different between groups, indicating that the CAI group experienced greater instability using the CAI limb during these tests. Conclusion: Clinical FPTs may identify subjective reports of instability, but fail to objectively measure performance deficits compared to the contralateral healthy limb in subjects with CAI.